CORPORATE SOCIAL RESPONSIBILITY EMPOWERMENT STRATEGY AT PT. SUNLIFE SHARIA FINANCIAL IN IMPROVING THE ISLAMIC WELL-BEING OF BABAKAN PEOPLE AT TANGERANG CITY - Nur Jamaludin; Mayang Faluthamia; Rizfandi Yahya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to find out Corporate Social Responsibility (CSR) Empowerment Strategy at PT. Sun Life Sharia Financial Tangerang city for the well-being of Babakan people. This research uses qualitative analysis method by means of data collection technique uses observations, comprehensive interviews and documentations. The Purposive sampling technique used in this research to choose the informants, namely by choosing the most informed interviewees about the topic of the research. Research finding shows that Corporate Social Responsibility (CSR) Empowerment Strategy at PT. Sun Life Sharia Financial Tangcity for the people well-being has been in accordance with the Company Operational Standard. However, in its practice, there are some notes regarding the strategy. First, the distribution is already well-executed even though there are some things that do not go according to Company’s plans. Second, in attempt of empowerment, PT. Sun Life has a program called Sun Bright, that is a social program which serves to help people in Welfare, Education, and Economic matters. Third, the People are truly satisfied by the help given by the Company. It improves their wellbeing such improve in economic, social, educational, and spiritual needs.